PENGARUH MOTIVASI BELAJAR DAN MANAJEMEN WAKTU TERHADAP PROKRASTINASI AKADEMIK PADA PEMBELAJARAN EKONOMI PESERTA DIDIK SMA NEGERI 3 SURABAYA - Munawaroh, Siti; Rafsanjani, Mohamad Arief (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to analyze th influence of learning motivation and time management on academis procrastination in economics learning among students at SMA Negeri 3 Surabaya. The background of this research lies in the phenomenon of delay or academic procrastination shown by students, particularly in the form of late submission of assignments given by their teacher. This study uses a quantitative method with Structural Equation Modelling (SEM) through WarPLS software. The sampling technique applied was proportional random sampling. The results show that learning motivation has a significant influence on academic procrastination, time management also has a significant influence on academic procrastination, and a simultaneous influence of learning motivation and time management on academic procrastination in economics learning at SMA Negeri 3 Surabaya.